Parameter Fisika Dan Biologi Untuk Menilai Kualitas Air Pada Kolam Tanah Untuk Budidaya Ikan Nila (Oreochromis Niloticus)Di Desa Mazingo Tanoseo Kecamatan Hiliduho - Harefa, Sesilia Viktoria (Jurnal Perikanan dan Kelautan, 2025)
Water quality is the main factor that influences the survival and productivity of fish in aquaculture systems, including the cultivation of tilapia (Oreochromis niloticus). Earthen ponds are a method that is widely used to cultivate tilapia, but optimal water quality control is needed so that the fish can thrive. Aquaculture or aquaculture is the breeding and care of animals and plants whose habitat is in water. Aquaculture refers to the cultivation and breeding of fish in special locations such as ponds and aquariums. This is done to increase the number of fish we eat or increase the fish population in nature. Types of fish that are used commonly cultivated include carp, salmon, tilapia and catfish. A pond is a piece of land that can hold a certain amount of water and is used to raise or cultivate fish. The Skills Education book states that pond cultivation has several special functions. The main function is to better organize fish cultivation. A pond is a piece of land that can hold a certain amount of water and is used to raise or cultivate fish. The Skills Education book states that pond cultivation has several special functions. The main function is to better organize fish cultivation.